Investigation of the effect of twisted tape turbulators on thermal-hydraulic behavior of parabolic solar collector with polymer hybrid nanofluid and exergy analysis using numerical method and ANN - Mustafa, Jawed; Alqaed, Saeed; Aybar, Hikmet S.; Husain, Shahid (Elsevier Sci Ltd, 2022)
In the present work, a study has been performed on increasing the heat transfer of parabolic solar collectors through modeling of twisted tapes inside the absorber tube containing nanofluid, using ANSYS19.2 software with Finite Volume Method (FVM). In this regard, two specimens of twisted tape with different number of channels is installed in the absorber tube having a constant wall heat flux (1200 W) in the range of Re numbers (25,000-5000) flows with different volume fractions (2-6%). Performance Evaluation Criterion (PEC), Nusselt Number (Nu) and solar collector efficiency (eta) have been defined and their changes have been investigated. And achieve high efficiency (2.18) at Re=25,000, phi=2%. Therefore, model two turbulator is more desirable from the point of view of thermal fluid dynamics. The exergy efficiency of the liquid containing nanoparticles with a volume fraction of 2% declined for Cases 2, and 1 by about 0.023% and 0.026%, respectively, with increasing velocity. The neural network was used to trend the effects of perturbation on Nu, PEC, and exergy efficiency. The neural network trended three parameters with high accuracy so that the maximum error was estimated below 3.8%.
Keywords: Parabolic solar collector; Twisted tape turbulator; Hybrid nanofluid; CFD; Performance Evaluation Coefficient; ANN